Agricultural Management Options for Climate Variability and Change: Sensor-Based, Variable-Rate Nitrogen Management - Wesley Porter; Ahmad Khalilian; Daniel Dourte; Clyde Fraisse (EDIS)
Nitrogen fertilizer cost represents about 10%–15% of total farm costs for corn, cotton, and wheat in the Southeastern United States. The efficiency of nitrogen use can be highly variable for producers, so a sensor-based, variable-rate nitrogen application (SVNA) system has been developed for irrigated and dryland row crops to reduce production costs. Using sensor-based N application, there is a minimum 20% reduction in N usage. If that rate reduction were applied to all the cotton, corn, and wheat grown in the United States, CO2 emissions from N fertilizer production would be decreased by 2.7 million tons. This 4-page fact sheet was written by Wesley Porter, Ahmad Khalilian, Daniel Dourte, and Clyde Fraisse, and published by the UF Department of Agricultural and Biological Engineering, July 2012.